2014
DOI: 10.4081/oncol.2014.256
|View full text |Cite
|
Sign up to set email alerts
|

Review of cisplatin and oxaliplatin in current immunogenic and monoclonal antibody treatments

Abstract: Platinum-based chemotherapy agents initially transformed cancer treatment. However their effectiveness peaked as combined regimes showed little additional benefit in trials. New research frontiers developed with the discovery that conventional chemotherapy can induce immunological cell death by recruiting high mobility group box 1 protein through T-cell immunity. Simultaneously monoclonal antibody agents (not effective as monotherapies) showed good results in combination with conventional chemotherapy. Some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 88 publications
(121 reference statements)
1
63
0
Order By: Relevance
“…Cisplatin is a commonly used chemotherapeutic drug[ 8 ], while pemetrexed is a recently developed compound that has been reported to have a favorable toxic effect against gastric cancer cell lines[ 12 ]. The combination of pemetrexed and cisplatin has been used to treat advanced lung adenocarcinoma and malignant mesothelioma [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cisplatin is a commonly used chemotherapeutic drug[ 8 ], while pemetrexed is a recently developed compound that has been reported to have a favorable toxic effect against gastric cancer cell lines[ 12 ]. The combination of pemetrexed and cisplatin has been used to treat advanced lung adenocarcinoma and malignant mesothelioma [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is a frequently used chemotherapeutic drug that plays an anti-cancer role by binding to genomic DNA, causing DNA damage and ultimately leading to cell death [ 8 10 ]. Previous studies have suggested that cisplatin induces cell death by down-regulating the telomerase activity of choroidal melanoma cells in a dose- and time-dependent manner [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the nonsynergistic drug combinations, highlighted in blue in the table, such as cisplatin + oxaliplatin and gemcitabine + 5‐FU may result from their similar mechanism of action. Both cisplatin and oxaliplatin are DNA alkylating agents forming platinated intra‐strand and inter‐strand cross‐link, interfering with DNA replication . While gemcitabine and 5‐FU are both belongs to nucleoside analog family of medication, which induces cell apoptosis by inhibiting the synthesis of new DNA .…”
Section: Introductionmentioning
confidence: 99%
“…1 Chemotherapy for CRC mainly relies on fluoropyrimidine compounds combined with platinum drugs, mainly cisplatin and its analogues carboplatin and oxaliplatin, being this latter the leading Ptbased drug for the treatment of this pathology. 2 Oxaliplatin (Eloxatin™) is a third-generation platinum compound approved by United States Food and Drug Administration (FDA) on 2002 for the treatment of advanced CRC. To date thousands of patients worldwide have been treated with oxaliplatin, especially in combination with other drugs.…”
Section: Introductionmentioning
confidence: 99%